(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Man has been using refrigeration in his everyday life since ancient times for a variety of purposes. The major changes which have taken place in this field over time include primarily trends in the way cooling conditions are created. After beginning using natural ice and sailing across a range of substances, including ammonia, hydrocarbons, etc., the usage of CFCs and HCFCs has now finally reached the stage. The usage of CFCs and HCFCs however leads to the imminent risks of global warming and ozone depletion. To date, a quantity of study has been carried out to complete the abolition of the usage of these CFCs and HCFCs on both the research and social fronts. Recently, the use of coolant mixtures is an effective way of identifying alternatives for the threatening coolant. R134a was recommended as an alternative coolant for R12, on the advent of the Montreal Protocol. In mineral oil R134a is not miscible. It is advised to use polyol ester (POE) synthetic oils. HC refrigerants, on the other side, have flammable properties and safety requirements that restrict the use in domestic equipment of pure HC refrigerants. Due to the above, it will be crucial for the cooling and air-conditioning industry to convert current R134a coolers into environmentally sound refrigerants. We also experimented with alternate refrigerants in this study.